FACTORS AND BENEFITS OF CLOUD COMPUTING - Mr. Anish D (International Journal of Advanced Science and Technology, 2019)
Cloud computing is rising fast and no uncertainty it is the next generation innovation where people will utilize anyplace and anytime. Cloud computing gives an extraordinary chance to empowering solid E-Governance rapidly at lower costs. Today clouds with virtualization are changing IT. Separated of its ubiquity it has a few concerns which are turning out to be groups for its more extensive adoption. Cloud computing gives a proficient, scalable, and cost- effective way for the present associations to convey business or customer IT services over the web. This paper centers on the key characteristics, components and data security.